2018
DOI: 10.1002/acr.23554
|View full text |Cite
|
Sign up to set email alerts
|

What Imaging‐Detected Pathologies Are Associated With Shoulder Symptoms and Their Persistence? A Systematic Literature Review

Abstract: ObjectiveShoulder symptoms are common, and imaging is being increasingly used to help with management. However, the relationship between imaging and symptoms remains unclear. This review aims to understand the relationship between imaging‐detected pathologies, symptoms, and their persistence.MethodsA systematic review using Medline, EMBASE, Cochrane, and grey literature was conducted to April 2017. The cross‐sectional and longitudinal relationships between imaging‐detected abnormalities and symptoms were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 76 publications
(464 reference statements)
1
20
0
1
Order By: Relevance
“…4 Neither clinical features nor diagnostic imaging can reliably pinpoint a specific nociceptive cause of rotator cuff disease from the numerous candidate pain-sensitive structures in the shoulder (eg, tendon, bursa). [5][6][7][8][9][10][11] Possibly as a result of such uncertainty, there are a plethora of diagnostic labels that have been used in both routine practice and research to indicate the same condition. 12 Some labels describe the clinical features (eg, painful arc syndrome), the Strengths and limitations of the study ► Our study used a large sample size and a highly reliable coding frameworks (k=0.90-0.97 across labelling groups for both questions).…”
Section: Introductionmentioning
confidence: 99%
“…4 Neither clinical features nor diagnostic imaging can reliably pinpoint a specific nociceptive cause of rotator cuff disease from the numerous candidate pain-sensitive structures in the shoulder (eg, tendon, bursa). [5][6][7][8][9][10][11] Possibly as a result of such uncertainty, there are a plethora of diagnostic labels that have been used in both routine practice and research to indicate the same condition. 12 Some labels describe the clinical features (eg, painful arc syndrome), the Strengths and limitations of the study ► Our study used a large sample size and a highly reliable coding frameworks (k=0.90-0.97 across labelling groups for both questions).…”
Section: Introductionmentioning
confidence: 99%
“…A recently published systematic review 33 found conflicting results regarding the association between imaging findings of the shoulder such as AHD and symptoms. This study only presented the results narratively, with no meta-analysis investigating the subacromial space differences between adults with SAPS and controls with no shoulder pain.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is conflicting evidence about the correlation between imaging findings and pain in the shoulder because pathologies may also exist in asymptomatic individuals. 36 It is not assumed that changes in the chronic stage of tendinopathy are reversible, but exercise may optimize the function of the remaining healthy tendon structure including improved elasticity and thereby function of the tendon. Elasticity is not measurable using existing imaging modalities, such as conventional US.…”
mentioning
confidence: 99%